Pemanfaatan Potensi Pertanian Desa Berbasis Nilai-Nilai Islam di Desa Awang Cenrana Kabupaten Bone - Fatmawati, Fatmawati; Danil, Harling; Fahmi, Muhammad; Risnawati, Risnawati; Fauzan, Naufal; Patiah, Andi Sitti; Farid. AR, M. Fadly Miftah; Maharani, Nabila; Nurfadillah, Nurfadillah; Alfarisy, Andi Muh. Nur (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Awang Cenrana Village has significant agricultural potential as a primary economic pillar for the community. These activities naturally embody Islamic ethical values. However, most residents are unaware of or do not yet conceptually understand these values ​​as part of an integrated Islamic value system in their work. This Community Service (PKM) activity aims to explore and internalize the potential of village agriculture based on Islamic values ​​to support sustainable and equitable agricultural development in Awang Cenrana Village. This activity was implemented through a participatory exploration approach and community mentoring. The activity stages included observing local agricultural practices, identifying spiritual values ​​embedded in the farmers' work ethic, and conducting outreach to provide a conceptual understanding of the integration of Islamic values ​​into natural resource management. The results of the activity indicate that Islamic values ​​such as honesty, trustworthiness, hard work, mutual assistance, and trust in God are deeply embedded in the community's agricultural activities. These values ​​have proven to play a crucial role as ethical guidelines that shape responsible work patterns, maintain social harmony, and support environmental sustainability. This integration balances the economic, social, and spiritual aspects of the village community. This activity contributes to a model for developing independent villages that integrates economic productivity with strengthening religious awareness. In addition to improving welfare, these results are expected to serve as a reference for other villages with similar characteristics in achieving balanced and sustainable development.